N Analysis of Lexical and Contextual Meaning in Elevation Worship’s Song Lyrics - Nurfithri, Nurfithri (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This research focusses on analyzing lexical and contextual meaning in Elevation worship’s song lyrics. By listening to the songs, we can get knowledge about appreciation literature and the background of the song. Therefore, the researchers were interested in analyzing the kinds of meaning used in Elevation Worship songs. The researchers dedicated to give the title of this research “An Analysis of Lexical and Contextual Meaning Elevation Worship’s Song Lyrics”. The problem of this research are: (1) what are the lexical and contextual meaning in the Elevation Worship’s Lyrics? (2) What percentage of the lexical words that contain the contextual meaning in the “Elevation Worship’s” song? The researchers took five songs from different album. This research uses a descriptive method by analyzing the research object of Elevation Worship Song Lyrics. To obtain the data, the researchers collected the data from Elevation Worship’s Song Lyrics and from internet. After that, the songs which contain lexical and contextual meanings were selected. The result of this research are as follows: (1) related to the lexical meaning, while (2) related to the contextual meaning. The researchers found 25 lexical words or 29.64% of five data that contain the contextual meanings. Thus, the researchers expect this research will be useful for the other researchers who are eager to obtain more knowledge about semantic field. Moreover, semantic is an important branch of linguistic that is interesting to be studied, especially when it is applied to literary works, such as songs or poem etc.